Characteristic of mobile satellite l-band signal in mid-latitude region:GPS approach - Voon Pai, B.; Abidin, W.A.W.Z; Othman, A.K.; Zen, H.; Masri, T. (NISCAIR-CSIR, India, 2011)
Mobile satellite L-band signal that propagates from the transmitting satellite to the receiver experiences impairment mainly due to shadowing and multipath effects. In the present study, open space data has been obtained for Fukuoka, Japan (mid-latitude) using portable global positioning system (GPS) satellite receiver. The received signal performance, fading characteristic and cumulative distribution function of certain GPS satellites over the sky of Fukuoka have been observed and analysed. A general mathematical model representing the signal strength for the open space environment has been deduced based on the collected data. The outcome of this study can be used in future research to determine the effect of different mobile satellite environment on the arriving mobile satellite signal in improving the quality of service perceived by mobile satellite users.